2002
DOI: 10.1007/s00468-002-0180-8
|View full text |Cite
|
Sign up to set email alerts
|

Relations between efficiency of water transport and duration of leaf growth in some deciduous and evergreen trees

Abstract: Shoot and leaf growth rate as well as shoot hydraulic conductance per unit leaf area (K SL ) were measured on three evergreen (Viburnum tinus L., Prunus laurocerasus L., Laurus nobilis L.) and three deciduous (Corylus avellana L., Juglans regia L., Castanea sativa L.) trees growing under the same environmental conditions. The times required to complete shoot growth (27 days for P. laurocerasus to 51 days for V. tinus) and leaf expansion (24 days for C. sativa to 42 days for C. avellana) were very different amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 36 publications
(39 reference statements)
1
13
0
1
Order By: Relevance
“…This relationship between root architecture, summer water potential, and/or phenology have been suggested by other authors (Borchert, 1978;Callaway et al, 1991;De Lillis and Fontanella, 1992;Meinzer et al, 1999). Although we cannot disregard other plant properties as contributors to the species different growth response to drought (see, for example, Fricke and Flowers, 1998;Lu and Neumann, 1999;Nardini, 2002), the root depth and the corresponding C differences suggest that they are major determinants of the phenological response to water shortage. The first peak of leaf abscission, which mostly affected previous-year leaves, occurred in June for both species, as typically observed in many sclerophyllous Mediterranean phanaerophytes (Castro-Dı´ez and Montserrat-Martı´, 1998).…”
Section: Comparison Of Species Performancesupporting
confidence: 80%
“…This relationship between root architecture, summer water potential, and/or phenology have been suggested by other authors (Borchert, 1978;Callaway et al, 1991;De Lillis and Fontanella, 1992;Meinzer et al, 1999). Although we cannot disregard other plant properties as contributors to the species different growth response to drought (see, for example, Fricke and Flowers, 1998;Lu and Neumann, 1999;Nardini, 2002), the root depth and the corresponding C differences suggest that they are major determinants of the phenological response to water shortage. The first peak of leaf abscission, which mostly affected previous-year leaves, occurred in June for both species, as typically observed in many sclerophyllous Mediterranean phanaerophytes (Castro-Dı´ez and Montserrat-Martı´, 1998).…”
Section: Comparison Of Species Performancesupporting
confidence: 80%
“…A previous study conducted in the same experimental plots showed that, without any adjustment of xylem vulnerability to embolism, lower water potentials undergone by the trees in the dry treatment were likely to reduce the xylem hydraulic conductivity, thus creating a need for a reduction of the leaf area in order to maintain the leaf specific conductivity (Limousin et al 2010a). Previous studies have reported strong correlations between shoot hydraulic conductance and shoot and leaf growth in several species (Nardini 2002;Cochard et al 2005). Cochard et al (2005) showed that the number of leaf primordia preformed inside beech buds was controlled by the hydraulic conductance of the supporting shoot.…”
Section: Drought-induced Reduction Of Shoot Growth and Leaf Areamentioning
confidence: 99%
“…duration of leaf growth; Nardini, 2002) besides stomatal conductance, net photosynthesis, and primary production. Drought tolerance (Sperry et al, 1998;Sperry, 2000;Martí-nez-Vilalta and Piñol, 2002), geographic distribution of species (Brodribb and Hill, 1999) and even type of photosynthetic pathway (Kocacinar and Sage, 2004) are considered to be associated with xylem hydraulic properties and with xylem vulnerability to cavitation in particular.…”
Section: Introductionmentioning
confidence: 99%